IMPLEMENTATION OF ISLAMIC RELIGIOUS PROJECT-BASED LEARNING AT MATARAM UNIVERSITY - Agus Kurnia; Lenny Herlina; Arif Nasrullah; Humamurrizqi (Universitas Islam Negeri Mataram, 2025)
Islamic Religious Education (PAI) learning in the modern era must be able to combine various methods to be more effective in accordance with the challenges of modern needs. The use of the lecture method needs to be integrated with other methods so that learners can be more student-centered so that they are more active in learning. Project-based learning is a solution by involving students in real projects that are relevant to life so that they can apply Islamic values contextually. This study aims to describe and analyze the application of the method in PAI courses at the University of Mataram using a qualitative approach through observation, interviews, and documentation that are analyzed thematically. The results of the study show that students are actively involved in problem-solving projects such as SDGs issues based on Islamic values. They showed improvements in critical thinking, communication, and collaboration. Although there are challenges such as lack of time for deepening Islamic materials. The benefits of this method strengthen academic and social skills for students, and provide education, practical solutions, and awareness of pressing social issues for society. In conclusion, this project-based learning is quite effective in improving the quality of Islamic learning and is recommended to be combined with various methods such as the lecture method to create more holistic, applicative, and directly beneficial learning for the wider community. This research makes a real contribution to developing education that not only focuses on theory but also produces positive social impacts.